PHYTOMEDICINE VERSUS GONORRHOEA: THE BAPEDI EXPERIENCE - Erasmus, Lourens Johannes Christoffel; Potgieter, Marthienus Johannes; Semenya, Silas Sebua; Lennox, Sandra Janet (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Records regarding the phytomedicine employed by the Bapedi are almost non-existent. This is the first study of herbal remedies used by Bapedi traditional healers to treat gonorrhoea, of concern as it is a danger to reproductive health. A semi-structured questionnaire, centred on sexual health, was administered to 30 traditional healers in 15 local municipalities across the three districts of Limpopo Province during 2009/10. The questionnaire focussed on the use of plants for medicine as well their application in reproductive health management. This investigation found that the Bapedi employed no less than 18 different plant species, sometimes as multiple-plant extracts, but more often as single-plant extracts. The single most used species was Catharanthus roseus, which accounted for 60% of all reported cases, followed by Aloe marlothii subsp. marlothii (13.3%). Both these species occur abundantly throughout the province and are currently not threatened. This is the first record for the use of Callilepis salicifolia, Jatropha zeyheri and Cotyledon orbiculata to treat gonorrhoea by people of any culture.